Sex Differences and Long-Term Outcome in Patients With Pacemakers - Riesenhuber, Martin; Spannbauer, Andreas; Rauscha, Friedrich; Schmidinger, Herwig; Boszotta, Adelinde; Pezawas, Thomas; Schukro, Christoph; Gwechenberger, Marianne; Stix, Günter; Anvari, Anahit; Wrba, Thomas; Khazen, Cesar; et al. (Frontiers in Cardiovascular Medicine, 2020)
Introduction Evidence of sex-related differences in patients with pacemakers regarding comorbidities is insufficiently investigated. The aim of this study was to determine the relationship of cardiovascular comorbidities and sex category with properties of pacemaker implantation, pacemaker follow-up, and long-term survival. Methods This retrospective, single-center cohort study consisted of 6362 pacemaker-patients (39.7% female) enrolled between May 2000 and April 2015. Functional pacemaker parameters were registered at regular pacemaker controls. Survival status and cause of death were analyzed in relation to comorbidities, implanted pacing devices, and echocardiography. Survival analyses were plotted for a 10-year follow-up. Results Patients with hypertension or hyperlipidemia had higher rates of implantations due to sick sinus syndrome (28.6% vs 25.5% without hypertension, P<0.001; 30.7% vs 25.7% without hyperlipidemia, P<0.001), while endocarditis was associated with higher rates of implantations due to AV block (46.7% vs 33.4%, P<0.001). Patients with valvular heart disease had higher rates of pacemaker implantation due to bradycardic atrial fibrillation (24.9% vs 21.0% without valvular heart disease, P<0.001). Ventricular pacing threshold increased in both sexes during the follow-up and was higher in women in the final follow-up (0.94 V vs 0.91 V in men, P=0.002). During the 10-years follow-up, 6.1% of women and 8.6% of men underwent lead replacement (P=0.054). Device and lead replacement rates were increased if the comorbidities coronary artery disease, heart failure, hypertension, hyperlipidemia, valvular heart disease, previous stroke/TIA, atrial arrhythmias, chronic kidney disease, or endocarditis were present. Diabetes and previous CABG increase the rates of device replacement, but not the rate of lead replacement. Severe tricuspid regurgitation after implantation of pacemaker was present in more men than women (14.4% vs 6.1%, P<0.001). In a multivariate COX regression, the following variables were associated with independent decrease of 10-year survival: hypertension (HR 1.34, 95% CI 1.09-1.64), chronic kidney disease (HR 1.83, 95% CI 1.53-2.19), tricuspid regurgitation after pacemaker implantation (HR 1.48, 95% CI 1.26-1.74). Survival was independently increased in female sex (HR 0.83, 95% CI 0.70-0.99) and hyperlipidemia (HR 0.81, 95% CI 0.67-0.97). Conclusions Cardiovascular comorbidities influenced significantly pacemaker implantations and long-term outcome. Trial Registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT03388281.